Invigoration of Expired Spinach Seeds (Amaranthus sp.) with Water Hyacinth Root Extract - Sagita, Erika Rizki; Rahayu, Yuni Sri (LenteraBio : Berkala Ilmiah Biologi, 2022)
Spinach seeds that have passed the expiration date can be increased their vigor and viability by invigorating treatment with natural plant growth regulators such as water hyacinth root extract. This study aims to determine the effect of seeds expiration date and concentration of water hyacinth root extract on the germination and growth of expired spinach seeds. This research used a Randomized Block Design with two factors and three replications. The first factor was the expired time of spinach seeds which were 1 month, 3 months, and 6 months. The second factor was the concentration of extract were 0 g/L, 25 g/L, 50 g/L, 75 g/L, and 100 g/L. This research was carried out at the Green House of Department of Biology, Faculty of Mathematics and Natural Sciences, from October to December 2021. The result was analyzed using two way ANOVA test and if the test result showed a significant value, it was continued with Duncan test at 5% level. The results showed that there was an influence between concentration and expiration time on germination parameters (vigor index, germination rate, speed of seed growth, and seed growth simultaneously) and growth parameters (plant height and wet biomass) of spinach seeds. The best result was shown in treatment with the concentration of water hyacinth extract 100 g/L with an average vigor index value was 75.56%, the germination rate was 75.56%, seed growth speed value was 57.85%/Etmal, seed growth simultaneously was 56.67%, plant height was 6.02 cm, and wet biomass was 5.89 grams.